Self-Injury Is My Drug: The Functions of Describing Nonsuicidal Self-Injury as an Addiction. Issue 9 (8th September 2021) - Pritchard, Tyler R.; Fedchenko, Chelsey A.; Lewis, Stephen P.
Abstract: Adolescents and emerging adults who engage in nonsuicidal self-injury (NSSI) often participate in online activity regarding their self-injury. Of particular importance are the potential benefits and risks associated with online NSSI activity, including how individuals describe their NSSI experiences. One way that individuals describe these experiences is by discussing NSSI as an addiction. Accordingly, we used thematic analysis to explore why individuals may use addiction references to describe their NSSI experiences. To do this, we examined 71 posts from a popular NSSI social network. Four themes emerged: difficulty inherent in stopping, authentication, warn others, and communicate the plight of the behavior. Findings highlight a number of avenues for research as well as implications for clinicians working with clients who self-injure perceive NSSI as an addiction. Mental health professionals can leverage their understanding of clients' perceptions of NSSI to better serve this population.